Identifying a novel connection between the fungal plasma membrane and pH‐sensing. Issue 4 (9th September 2018) - Brown, Hannah E.; Ost, Kyla S.; Esher, Shannon K.; Pianalto, Kaila M.; Saelens, Joseph W.; Guan, Ziqiang; Andrew Alspaugh, J.
Summary: The mechanisms by which micro‐organisms sense and internalize extracellular pH signals are not completely understood. One example of a known external pH‐sensing process is the fungal‐specific Rim/Pal signal transduction pathway. Fungi, such as the opportunistic pathogen Cryptococcus neoformans, use Rim signaling to sense and respond to changes in environmental pH. Mutations in this pathway result in strains that are attenuated for survival at alkaline pH, and often for survival within the host. Here, we used an insertional mutagenesis screen to identify novel genes required for C. neoformans growth at host pH. We discovered altered alkaline pH growth in several strains with specific defects in plasma membrane composition and maintenance of phospholipid assembly. Among these, loss of function of the Cdc50 lipid flippase regulatory subunit affected the temporal dynamics of Rim pathway activation. We defined distinct and overlapping cellular processes regulated by Rim101 and Cdc50 through analysis of the transcriptome in these mutant strains. We further explored how pH‐induced membrane changes affect membrane‐bound pH‐sensing proteins, specifically the C‐terminal domain of the Rra1 protein, an upstream Rim pathway activator and pH sensor. These results suggest both broadly applicable and phylum‐specific molecular interactions that drive microbial environmental sensing. Abstract : In order to survive in a stressful environment, microbes must sense and respond to changes in external pH. Cryptococcus neoformans uses the fungal specific alkaline response Rim pathway and its membrane‐associated pH sensor, Rra1, to sense changes in pH. This study explores how Rra1, specifically its flexible C‐terminal tail, differentially localizes to the membrane in response to pH‐induced changes to the fungal plasma membrane.